Construction of Versatile Advanced Micro Processor based Controller for Spray Pyrolysis Unit and Study of Characterization of Nano Crystalline Tin Oxide (SnO2) Thin Films - V. Uma*, V. Chaitra, K.S. Shamala (Recent Research in Science and Technology, 2011)
Significant improvements in coating deposition control can be achieved with advanced micro processor based controller for spray pyrolysis coating technology that provides precise control of film thickness for the application of thin films and Photo resist to wafers. FY series Digital PID controllers are used in this system for deposition of thin as well as nano structural materials. In this paper we compare advanced system with old traditional system. This is more reliable, more economical for the laboratory and small-scale industries. Nano grain sized tin-oxide (SnO2) films have been prepared through microprocessor controlled spray pyrolysis unit. The polycrystalline nature of SnO2 film was characterized by XRD. The homogenous and continuous film was confirmed by SEM micrographs. The films exhibited transmittance, around 70%, in the visible region. The optical band gap found to be 3.6 eV. Work-hardening index was found to be 0.5, which revels the material is hard.